A review of European studies on pollination networks and pollen limitation, and a case study designed to fill in a gap. Issue 6 (31st October 2018) - Bennett, Joanne M; Thompson, Amibeth; Goia, Irina; Feldmann, Reinart; Ştefan, Valentin; Bogdan, Ana; Rakosy, Demetra; Beloiu, Mirela; Biro, Inge-Beatrice; Bluemel, Simon; Filip, Milena; Madaj, Anna-Maria; et al.
Abstract: Anthropogenic environmental change disrupts interactions between plants and their animal pollinators. To assess the importance of different drivers, baseline information is needed on interaction networks and plant reproductive success around the world. We conducted a systematic literature review to determine the state of our knowledge on plant–pollinator interactions and the ecosystem services they provide for European ecosystems. We focussed on studies that published information on plant–pollinator networks, as a community-level assessment of plant–pollinator interactions and pollen limitation, which assesses the degree to which plant reproduction is limited by pollinator services. We found that the majority of our knowledge comes from Western Europe, and thus there is a need for baseline assessments in the traditional landscapes of Eastern Europe. To address this data gap, we quantified plant–pollinator interactions and conducted breeding system and pollen supplementation experiments in a traditionally managed mountain meadow in the Western Romanian Carpathians. We found the Romanian meadow to be highly diverse, with a healthy plant–pollinator network. Despite the presence of many pollinator-dependent plant species, there was no evidence of pollen limitation. Our study is the first to provide baseline information for a healthy meadow at the community level on both plant–pollinator interactions and their relationship with ecosystem function (e.g. plant reproduction) in an Eastern European country. Alongside the baseline data, we also provide recommendations for future research, and the methodological information needed for the continued monitoring and management of Eastern European meadows. Abstract : Our goal was to identify and bring awareness to research gaps in European pollination ecology. By systematically searching literature on plant–pollinator networks and pollen limitation we found a strong Western European bias in the location of studies and no baseline assessment of plant–pollinator interaction in Eastern European landscapes. To address this data gap, we quantified plant–pollinator interactions and conducted breeding system and pollen supplementation experiments in a traditionally managed meadow in the Eastern Romanian Carpathians. For future research, we provide the methodological information to continue monitoring and managing the meadows of Eastern Europe.